Customer satisfaction towards service centre at Perodua Sales Sdn. Bhd. Kuching Branch / Razami Mohamad Jamali - Mohamad Jamali, Razami Mohamad (2002)
Providing a high level of customer satisfaction and service is considered as one of the prime ways to curb or fight against competition. Besides it is one way for the customers to differentiate between the service provided and the customers should determine the service quality. This research is to determine the customer satisfaction on the service with regards to facilities, customer services and service centre locality of Perodua service centre at PSSB Kuching Branch. Finding from the study generally show that customers consider most of the service and facilities provided as average. However, there are certain areas of the service that customers considered as good such as locality, frontline service, availability of waiting room, its cleanliness and entertainment provided, helpfulness of employees and speed of customer service. The critical area which customers considered as poor is the speed of the car service especially during peak hours.